PENGARUH LIKUIDITAS SOLVABILITAS DAN SAHAM MANAJERIAL TERHADAP PROFITABILITAS: (Studi Kasus pada Perusahaan Farmasi yang terdaftar di Bursa Efek Indonesia Periode 2011-2020) - Nursafitri; Nurman; Andi Mustika Amin (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to test the Effect of Liquidity, Solvency and Managerial Shares on Profitability (Case Study on Pharmaceutical Companies listed on the Indonesia Stock Exchange Period 2011-2020). The population in this study was 10 pharmaceutical companies and the sample in this study was 7 pharmaceutical companies with sample determination using the purposive sampling method. This research method uses quantitative methods and the data analysis method used is multiple regression analysis. This study used primary data by conducting research on 7 pharmaceutical companies listed on the IDX for the 2011-2020 period. The results showed that liquidity, solvency and managerial stocks had a simultaneous positive and significant effect on profitability. This means that the higher the liquidity, solvency and managerial shares of pharmaceutical companies, the more it will increase the profitability of pharmaceutical companies listed on the IDX for the 2011-2020 period.